Loss of TIPE2 Has Opposing Effects on the Pathogenesis of Autoimmune Diseases - Liu, Ruiling; He, Xiaozhen; Geng, Wenwen; Wang, Ting; Ruan, Qingguo (Frontiers in Immunology, 2019)
Autoimmune diseases are a physiological state wherein immune responses are directed against and damage the body's own tissues. Cytokines secreted by infiltrated inflammatory cells contribute to the pathogenesis of autoimmune diseases. TIPE2, one of the four family members of Tumor necrosis factor-α induced protein-8 (TNFAIP8), is a negative regulator of innate and adaptive immunity and plays essential roles in the maintenance of immune tolerance. However, studies on the role of TIPE2 during the development of autoimmune diseases have generated contradictory results. In the current study, we sought to determine the role of TIPE2 during the development of IMQ-induced psoriasis and Experimental Autoimmune Uveitis (EAU) in mice. Our study revealed that, while TIPE2-deficiency alleviates psoriasis, it exacerbates the development of EAU. Further studies demonstrated that, although TIPE2-deficient T cells produced more IL-17A, they do not migrate efficiently to the local inflammatory site, i.e., the skin. This in turn led to the decreased IL-17A production in the skin and consequently reduced the severity of psoriasis in TIPE2-deficient mice. However, although TIPE2-deficient T cells still produced more IL-17A in EAU model, they migrate into the inflamed eye as efficient as TIPE2-sufficient T cells, and consequently exacerbates the development of EAU in TIPE2-deficient mice. Taken together, these results indicate that TIPE2 may either promote or suppress autoimmunity depending on the specific inflammatory microenvironment in different types of autoimmune diseases.